Metacarpal Shortening with Intramedullary Screw Fixation: A Cadaveric Study - Kwan, Stephanie A.; Wang, William L.; Tulipan, Jacob E.; Kachooei, Amir; Beredjiklian, Pedro K.; Rivlin, Michael (Journal of Wrist Surgery, 2022)
Background Intramedullary screw fixation is a commonly used technique for the management of metacarpal fractures. However, compression across the fracture site can lead to unintentional shortening of the metacarpal.Questions/Purposes Our aim was to evaluate the risk of overshortening with differing intramedullary device designs for fixation of metacarpals.Methods The small finger metacarpal of nine fresh-frozen cadavers were included. A metacarpal neck fracture was simulated with a 5-mm osteotomy. Three different intramedullary screw designs were compared. Each screw was placed in a retrograde fashion into the intramedullary canal and the amount of shortening measured. Screws were reversed and the number of reverse turns with the screwdriver needed to release overshortening were measured.Results The average shortening at the osteotomy site was 2.5 mm. The mean shortening was 80%, 58%, and 12% for the partially threaded screw, fully threaded screw, and threaded nail, respectively. The mean differences of the distance shortened were statistically significant for the threaded nail compared with the partially and fully threaded screws. The partially threaded screw had the most shortening, while the threaded nail provided the least amount of shortening. When the screws were reversed, the screws did not disengage until the screw was fully removed from the osteotomy site.Conclusion The fully threaded nail demonstrates less shortening and possibly minimizes overshortening of fractures compared with partially threaded and fully threaded screw designs. Overshortening cannot be corrected by unscrewing the screw unless completely removed from the distal fragment.Clinical Relevance Orthopaedic surgeons may select intermedullary screws based on the design that is suited for the particular metacarpal fracture pattern.
Keywords: metacarpal; fracture; treatment; intramedullary screw